GASTOMER MENINGKATKAN PEREKONOMIAN MASYARAKAT LOKAL PAPUA - Retno Wuri Sulistyowati; Adi Sumarsono; Diah Harmawati; Mega Suteki; Ni Luh Putu Nita Yulianti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Buti Village, located on Arafura Street, Merauke Regency, South Papua Province, is home to Indigenous Papuans (OAP) from the Marind Tribe whose livelihoods are closely connected to traditional fishing activities. The village is endowed with local fishery resources, particularly gastor fish (Channa striata), which has the potential to be further developed into value-added products to support community-based economic activities. Strengthening the capacity of local communities through skills development and entrepreneurship support is therefore considered an important step in optimizing this local potential. This community service activity was designed to support community empowerment through entrepreneurship training and hands-on assistance in processing gastor fish into marketable products. The activities were carried out through several stages, including mapping local potential, technical training on fish processing, assistance in packaging and branding, and basic marketing guidance. The program resulted in the development of five gastor-based products marketed under the GASTOMER brand, including fish crackers, nuggets, shredded fish (abon), gastor chili sauce, and organic fertilizer derived from fish waste. Beyond product development, the program also contributed to improving practical skills, encouraging community participation in small-scale entrepreneurship, and supporting local economic initiatives based on available resources. Overall, the activity highlights the importance of community-based empowerment programs as a practical approach to strengthening local capacities and supporting sustainable economic development in Buti Village. ABSTRAK Kampung Buti di Jalan Arafura, Kabupaten Merauke, Provinsi Papua Selatan merupakan kampung yang mayoritas dihuni oleh Orang Asli Papua (OAP) dari Suku Marind dengan mata pencaharian utama di sektor perikanan. Kampung ini memiliki potensi sumber daya ikan gastor (Channa striata) yang cukup melimpah dan berpeluang untuk dikembangkan menjadi produk olahan bernilai ekonomi. Namun, pemanfaatan potensi tersebut masih memerlukan penguatan melalui peningkatan keterampilan pengolahan, manajemen usaha, dan inovasi produk. Kegiatan Pengabdian Kepada Masyarakat ini bertujuan untuk meningkatkan kapasitas masyarakat melalui pelatihan kewirausahaan dan pendampingan pengolahan ikan gastor menjadi produk UMKM. Metode yang digunakan adalah pendekatan partisipatif melalui tahapan identifikasi potensi, pelatihan produksi, pendampingan pengemasan dan pelabelan, serta penguatan strategi pemasaran produk. Hasil kegiatan menunjukkan bahwa masyarakat mampu menghasilkan lima produk olahan ikan gastor dengan merek GASTOMER yaitu kerupuk, nugget, abon, sambal ikan gastor, dan pupuk organik berbahan limbah ikan yang memiliki nilai ekonomis. Kegiatan ini juga meningkatkan keterampilan masyarakat dalam pengolahan produk, menumbuhkan semangat kewirausahaan, serta membuka peluang pengembangan ekonomi keluarga berbasis potensi lokal. Dengan demikian, program ini menunjukkan bahwa pemberdayaan masyarakat berbasis sumber daya lokal dapat menjadi strategi yang efektif dalam mendorong kemandirian ekonomi dan penguatan kapasitas masyarakat Kampung Buti.